Bryophyte species richness on retention aspens recovers in time but community structure does not. - Anna Oldén; Otso Ovaskainen; Janne S Kotiaho; Sanna Laaka-Lindberg; Panu Halme (PLoS ONE)
Green-tree retention is a forest management method in which some living trees are left on a logged area. The aim is to offer 'lifeboats' to support species immediately after logging and to provide microhabitats during and after forest re-establishment. Several studies have shown immediate decline in bryophyte diversity after retention logging and thus questioned the effectiveness of this method, but longer term studies are lacking. Here we studied the epiphytic bryophytes on European aspen (Populus tremula L.) retention trees along a 30-year chronosequence. We compared the bryophyte flora of 102 'retention aspens' on 14 differently aged retention sites with 102 'conservation aspens' on 14 differently aged conservation sites. We used a Bayesian community-level modelling approach to estimate the changes in bryophyte species richness, abundance (area covered) and community structure during 30 years after logging. Using the fitted model, we estimated that two years after logging both species richness and abundance of bryophytes declined, but during the following 20-30 years both recovered to the level of conservation aspens. However, logging-induced changes in bryophyte community structure did not fully recover over the same time period. Liverwort species showed some or low potential to benefit from lifeboating and high potential to re-colonise as time since logging increases. Most moss species responded similarly, but two cushion-forming mosses benefited from the logging disturbance while several weft- or mat-forming mosses declined and did not re-colonise in 20-30 years. We conclude that retention trees do not function as equally effective lifeboats for all bryophyte species but are successful in providing suitable habitats for many species in the long-term. To be most effective, retention cuts should be located adjacent to conservation sites, which may function as sources of re-colonisation and support the populations of species that require old-growth forests.